Pre Feed Aspirates vs Abdominal Girth Monitoring for Detection of Feed Intolerance in VLBW Babies - Shiv Prasad Dubey; Ashish Jain; Nisha Kumar; Anjoo Bhatnagar; Veena Devgan (JCDR Research and Publications Pvt. Ltd., 2018)
Introduction: Feed intolerance is well known in Neonatal Intensive Care Unit (NICU) and is linked to morbidity and mortality in Very Low Birth Weight (VLBW) babies. Most definitions of feed intolerance include one or more of clinical criteria's viz. pre feed Gastric Residual Volumes (GRVs), colour of gastric aspirates, abdominal distension, emesis, bloody stools and clinical deterioration (increase in apnoea and/or bradycardia) resulting in discontinuation of feeding. But clinical significance of each of these criteria has not been studied systematically. Aim: To compare the role of abdominal girth monitoring vs pre feed residuals in prediction of feed intolerance, fasting hours, time to reach full feeds, incidence of Necrotizing Enterocolitis (NEC) II, and weight gain in VLBW babies. Materials and Methods: This prospective, two centre trial was conducted in the NICUs of two Tertiary Care Hospitals. Total 60 VLBW babies (30 from each hospital) on gavage feeding were enrolled. VLBW babies on gavage feeds at Faridabad Escort Hospital (FEH)-Pre feed Aspiration group (PA) and Hindu Rao Hospital (HRH)-Abdominal Girth monitoring group (AG) were studied. The outcome variables were vomiting, apnoea, bradycardia, fasting hours, days to reach full feeds, NEC-II and weight gain. Results: Lesser feed were found in AG group and fasting hours (p=0.015), days to reach full feeds (p=0.001) were significantly less and weight gain (p=0.02) was significantly more in AG group as compared to PA group. Conclusion: Monitoring feed intolerance by pre feed abdominal girth had advantage of better weight gain and fewer fasting hours and days to reach full feeds compared to pre feed aspiration in VLBW babies. Abdominal girth monitoring is less invasive and equally effective as pre feed aspiration.